Upaya Meningkatkan Hasil Belajar Matematika Pada Perkalian Dengan Menerapkan Media Stik Es Krim Dan Papan Perkalian Dikelas II SDN 01 Sukamadang - Ardila Ardila; Fauzi Fadliansyah (Desanta Publisher, 2024)
The application of the blended learning model combined with the environment of ice cream sticks and multiplication boards can maximize teaching and learning outcomes on geometry material for grade 2 elementary school students. The aim of this research is to describe the application of the blended learning model using the media method of ice cream sticks and multiplication boards and to compare the learning outcomes of class 2 students at SDN 01 SUKAMADANG in implementing blended learning using concrete object media on geometric material to improve this research is a cohort study (PTK) . The results of this research are (1) This research has four stages in each cycle. The planning stage is creating research instruments. The observation stage of this research increased teacher performance from Cycle I from 75% to 88% in Cycle II and student performance increased from Cycle I to 90% in Cycle II, and the final stage was reflection. (2) The classical perfection ratio of student learning outcomes is 54% in the initial stage, 71% in the first stage and 89% in the second stage. In conclusion, teachers can use this research as a reference to improve the learning outcomes of class II students in multiplication material.